Moral Bargain Hunters Purchase Moral Righteousness When it is Cheap: Within-Individual Effect of Stake Size in Economic Games - Yamagishi, Toshio (Sci Rep, 2016)
Despite the repeatedly raised criticism that findings in economic games are specific to situations involving trivial incentives, most studies that have examined the stake-size effect have failed to find a strong effect. Using three prisoner’s dilemma experiments, involving 479 non-student residents of suburban Tokyo and 162 students, we show here that stake size strongly affects a player’s cooperation choices in prisoner’s dilemma games when stake size is manipulated within each individual such that each player faces different stake sizes. Participants cooperated at a higher rate when stakes were lower than when they were higher, regardless of the absolute stake size. These findings suggest that participants were ‘moral bargain hunters’ who purchased moral righteousness at a low price when they were provided with a ‘price list’ of prosocial behaviours. In addition, the moral bargain hunters who cooperated at a lower stake but not at a higher stake did not cooperate in a single-stake one-shot game.